Separating the direct effect of hypoxia from the indirect effect of changes in cardiac output on the maximum pressure difference across the tricuspid valve in healthy humans. - Balanos, G; Talbot, N; Robbins, P; Dorrington, K (2005)
In healthy humans, changes in cardiac output are commonly accommodated with minimal change in pulmonary artery pressure. Conversely, exposure to hypoxia is associated with substantial increases in pulmonary artery pressure. In this study we used non-invasive measurement of an index of pulmonary artery pressure, the maximum systolic pressure difference across the tricuspid valve (DeltaPmax), to examine the pulmonary vascular response to changes in blood flow during both air breathing and hypoxia. We used Doppler echocardiography in 33 resting healthy humans breathing air over 6-24 h to measure spontaneous diurnal variations in DeltaPmax and cardiac output. Cardiac output varied by up to approximately 2.5 l/min; DeltaPmax varied little with cardiac output [0.61+/-0.74 (SD) mmHg min l(-1)]. Eight of the volunteers were also exposed to eucapnic hypoxia (end-tidal PO2 = 50 mmHg) for 8 h. In this group DeltaPmax rose progressively from 21 mmHg to 37 mmHg over 8 h. By comparing diurnal variations in DeltaPmax during air breathing with changes in DeltaPmax during hypoxia in the same eight individuals, we concluded that only approximately 5% of the changes in DeltaPmax during hypoxia could be attributed to concurrent changes in cardiac output. The low sensitivity of DeltaPmax to changes in cardiac output makes it a useful index of hypoxic pulmonary vasoconstriction in healthy humans.